2018
DOI: 10.1371/journal.pone.0201558
|View full text |Cite
|
Sign up to set email alerts
|

Bird-building collision risk: An assessment of the collision risk of birds with buildings by phylogeny and behavior using two citizen-science datasets

Abstract: Bird collisions with buildings are the second largest anthropogenic source of direct mortality for birds (365–988 million birds killed annually in the United States). Recent research suggests that this mortality occurs disproportionately across species. However, previous work had relied on regional and annual measures of relative species abundance. Our research identifies which species experience higher or lower collision rates than expected from local abundances using two sets of citizen science data: Minneso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…If species traits contribute to collision risk, we expect vulnerability estimates to be both repeatable across different studies, and also more similar among closely-related species, as found in a previous study of a single metropolitan region [11].…”
Section: Introductionmentioning
confidence: 60%
See 4 more Smart Citations
“…If species traits contribute to collision risk, we expect vulnerability estimates to be both repeatable across different studies, and also more similar among closely-related species, as found in a previous study of a single metropolitan region [11].…”
Section: Introductionmentioning
confidence: 60%
“…We compiled estimates of species collision vulnerability from four previous studies that surveyed bird collision fatalities in North America, and that focused primarily on large buildings during spring and fall migration seasons [1,3,10,11] (see Table S1 for details of each study). Two of the studies were conducted at a continent-wide scale, while the other two focused on single metropolitan areas; all four studies differed substantially in monitoring protocol and coverage.…”
Section: (A) Species Collision Vulnerabilitymentioning
confidence: 99%
See 3 more Smart Citations